Prevalence and predictors of workplace violence against emergency physicians in China: a cross-sectional study - Shijiao Yan; Jing Feng; Yong Gan; Rixing Wang; Xingyue Song; Zhiqian Luo; Xiaotong Han; Chuanzhu Lv (BMC, 2023)
Abstract Background Workplace violence (WPV) is considered a global problem, particularly in the health sector; however, no studies have assessed the national prevalence of WPV against emergency physicians and the associated factors in China. Methods A national cross-sectional survey was conducted in 31 provinces/autonomous regions/municipalities across China between July 2019 and September 2019. A total of 15 455 emergency physicians were selected using a multistage stratified random sampling method. A structured self-administered questionnaire was used to collect information on WPV and potential associated factors among emergency physicians. Descriptive and multivariable logistic regression analyses were used to identify the predictors of WPV. Results A total of 14 848 emergency physicians responded effectively (effective response rate: 96.07%). Of the respondents, 90.40%, 51.45%, and 90.00% reported exposure to any type of WPV, physical or nonphysical violence in the preceding year, respectively. Verbal aggression (87.25%) was the most common form of violence, followed by threat (71.09%), physical assault (48.24%), verbal sexual harassment (38.13%), and sexual assault (19.37%). Patients' families were the main perpetrators of these incidents. Unmet patient needs, taking drugs or drinking, and long waiting times were the main contributors to WPV. Physicians who were from low-developed regions, female, and without shift work were less likely to have experienced any type of WPV. Chinese emergency physicians who were from medium-developed regions, had a bachelor's degree, worked in a higher level hospital, had a higher professional title, with lower incomes, had a history of hypertension or coronary heart disease, were smokers or drinkers, and worked in hospitals without preventive measures or training for WPV and not encouraging to report WPV were more likely to have experienced any type of WPV. The predictors of WPV varied in different types of WPV. Conclusions This study shows that the prevalence of WPV against emergency physicians is high in China. Measures should be taken at the physicians, patients, hospital, and national levels to protect GPs from WPV; for example, improving physicians' level of service and hospital' reporting procedures. Creating a prevention strategy and providing a safer workplace environment for emergency physicians should be prioritized.